CALLI INDUCTION OF SOME CHILI PEPPER (Capsicum annuum L.) GENOTYPES AS MATERIAL FOR GENETIC TRANSFORMATION - Renfiyeni, Yusniwati, Jumsu Trisno and Jamsari (International Journal of Agricultural Sciences, 2015)
Calli is one of the materials used for genetic transformation. Studies on calli induction in some pepper genotypes were conducted in the Plant Tissue Culture Laboratory of the Faculty of Agriculture, Andalas University, Padang. This study aimed to obtain calli which can be used as material for genetic transformation. We used three genotypes of chili (Kopay, Kampung and Trisula). Explants were derived from first leaf, cotyledon, epycotyl and hypocotyl obtained from 24 days old chili germination. The study found that all the explants were able to produced calli. From 17 combinations of medium, the two combinations that produced 100% calli were MS + BAP + IAA + L2 vitamin and MS + 2,4 D. Mediums that can produce organogenic calli were MS + BAP 4 mg / L, IAA 0.5 mg / L, L2 vitamin ( Pyridoxin hydroklorit 0.5 g / L  and Thiamin hydroklorit 0.1 mg / L). The colour of calli produced were yellowish green and compact. The study also found that structures develop with a globular phase, followed by a heart shape, torpedo, cotyledonary and eventually form buds. While MS + 2.4 D 4 mg / L produced yellowish white calli and crumb, it could not grow organogenic calli.